2002
DOI: 10.1161/01.str.0000014773.57733.3e
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Hemorrhage

Abstract: Background and Purpose-Subarachnoid hemorrhage (SAH) caused by ruptured intracranial aneurysm affects approximately 16 000 Americans annually, and almost 40% of affected patients die within 30 days despite the best current therapy. Prevention of SAH is therefore of paramount importance. We present a preliminary analysis of risk factors for SAH from our population-based, case-control study. Methods-Cases were prospectively collected and matched 2:1 by age, race, and gender to controls using random digit dialing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(83 citation statements)
references
References 51 publications
6
75
0
2
Order By: Relevance
“…Most of the aneurysms were small: 2 IAs were ≥7 mm in maximal diameter; 19 were 4-6 mm; and 50 were 2-3 mm. Aneurysms arose most commonly on the ICA, with 31 such lesions (8 OphA, and 23 other ICA), followed in frequency by the MCA (20), PCoA (8), anterior cerebral artery (7), ACoA (3), and other locations (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the aneurysms were small: 2 IAs were ≥7 mm in maximal diameter; 19 were 4-6 mm; and 50 were 2-3 mm. Aneurysms arose most commonly on the ICA, with 31 such lesions (8 OphA, and 23 other ICA), followed in frequency by the MCA (20), PCoA (8), anterior cerebral artery (7), ACoA (3), and other locations (2).…”
Section: Resultsmentioning
confidence: 99%
“…Several uncommon heritable disorders are associated with brain aneurysms, including autosomal-dominant polycystic kidney disease, 3 Marfan syndrome, 17 Ehlers-Danlos syndrome Type IV, 4 hereditary hemorrhagic telangiectasia, 11 pseudoxanthoma elasticum, multiple endocrine neoplasia Type I, and neurofibromatosis Type 1. 16 Outside of these rare heritable disorders, population-based 8,18 and nonpopulationbased 10,[12][13][14] data suggest that there is an increased occurrence of IA and SAH in first-and second-degree relatives of those with SAH, with the highest risk being noted in siblings. Selected factors such as older age, female sex, history of hypertension, higher lipid levels, and elevated blood glucose have been suggested to increase the possibility of aneurysm detection in this setting.…”
mentioning
confidence: 99%
“…Environmental factors, such as cigarette smoking, hypertension and female gender, are known to be associated with IA. [3][4][5] Furthermore, several studies suggested an increased occurrence of IA and SAH in first-and second-degree relatives of SAH, with the incidence rate of 6-10%. [6][7][8][9] Several Mendelian disorders, such as autosomal-dominant polycystic kidney disease and Ehlers-Danlos syndrome type IV are associated with an increased risk of IA formation.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory and immunological reactions were also thought to be related to IA formation and rupture. In addition to ambient factors, epidemiological studies have demonstrated a familial influence contributing toward the pathogenesis of IAs, with an increased frequency in first-and second-degree relatives of people with SAH (Kissela et al, 2002).…”
Section: Discussionmentioning
confidence: 99%